Food for thought - Zawawi, Dahlia (Universiti Putra Malaysia Press, 2011)
This case revolves around a food company called Wharton Food (Malaysia) Berhad, a leading food manufacturer in Malaysia. Wharton Food is an international organization originating in New Zealand. It was founded in 1866 and it had grown into a huge organization employing over 200,000 people in more than 500 factories worldwide. The organization has a presence in most countries in the world with well diversified product lines in the industry including Malaysia. Wharton Food Malaysia moved from a hierarchical organization to a more flexible and dynamic network following the direction of Wharton Food. The change was intended to produce an alert and inventive organization as a flat and flexible structure were assumed to be able to increase efficiency, motivate employees, and enable the organization to foster the organization’s image as an attractive employer. This case highlights problems related to organizational change specifically on the issue of performance appraisal. The case presents an opportunity for post graduate and undergraduate students to apply their knowledge on a real life situation. This case has a moderate level of difficulty and may be used in the relevant management classes such as Human Resources and Organizational Behavior.